ECONOMIC AND TECHNOLOGICAL SUPPORT FOR THE DEVELOPMENT OF TOBACCO INDUSTRY IN PERSONAL PEASANT FARMS (INNOVATIVE ECONOMY, 2025)
Bialkovska H.D., Pashchenko V.I., Yurechko А.А., Vozniak H.M. ECONOMIC AND TECHNOLOGICAL SUPPORT FOR THE DEVELOPMENT OF TOBACCO INDUSTRY IN PERSONAL PEASANT FARMSPurpose. The purpose of the article is to study the existing problems and prospects for the development of tobacco in private peasant farms, to substantiate the economic and technological principles of growing tobacco varieties of Ukrainian selection with high yield and good quality of raw materials.Methodology of research. The following methods were used in the work: bibliographic and the method of theoretical analysis of scientific literary sources – during the study and analysis of modern scientific works of scientists regarding the problems of the development of personal peasant farms in Ukraine, that function in crop production; statistical, analysis and synthesis – during the study of the dynamics and structure of tobacco production by categories of farms; tabular – during the study of the dynamics of production, yield of tobacco; sociometric (questionnaire survey and sample survey of owners of households engaged in tobacco cultivation.Findings. The current state and trends in the development of tobacco in private peasant farms were analysed, the main factors for increasing the efficiency of tobacco production were determined, and the structure of cultivated areas was developed. Necessary measures are proposed to ensure the improvement of the quality characteristics of tobacco products in personal peasant farms of the population.Originality. The substantiation of the economic and technological principles of growing tobacco varieties of Ukrainian selection, which have high yields and good quality of raw materials in private households, has been further developed. A questionnaire was developed for surveying the owners of personal peasant farms engaged in tobacco cultivation.Practical value. The scope of application is personal peasant farms engaged in tobacco cultivation.Key words: personal peasant farms; tobacco; sort; crop capacity; gross collection; crop rotation; elite and reproductive seeds.
Keywords: personal peasant farms; tobacco; sort; crop capacity; gross collection; crop rotation; elite and reproductive seeds.